PARTICIPATION OF PREGNANT MOTHERS IN THE TRIPLE ELIMINATION PROGRAM FOR HIV, SYPHILIS AND HEPATITIS B DURING THE COVID-19 PANDEMIC IN MATARAM CITY, 2021 - WD, Siti Mardiyah; Pamungkas, Catur Esty; Amini, Aulia; Cahyaningtyas, Dwi Kartika (Siklus : Journal Research Midwifery Politeknik Tegal, 2022)
Background: The Covid-19 pandemic that hit almost all countries in the world today has had an impact on various health and non-health sectors, including the island of Lombok. Perinatal transmission from mother to baby is still quite high, as evidenced by 28,314 pregnant women who were tested for HIV in January-September 2012, as many as 812 pregnant women (2.9%) were infected with HIV. The Covid-19 pandemic has made the NTB government respond by issuing various policies to break the chain of transmission and reduce the impact that occurs, namely by locking, so that it has an impact on visits by pregnant women to carry out ANC checks to health services.Purposes: This study aims to explore the participation of pregnant women in the Triple Elimination Program for HIV, Syphilis, and Hepatitis B in the Covid-19 Pandemic in Mataram City.Methods: This study uses a qualitative and quantitative approach with descriptive analytic design with a cross-sectional design to determine the relationship between the independent variable and the dependent variable simultaneously in a single population and at the same time. Data analysis includes univariable analysis to describe the frequency distribution of each variable.Results: In general, the Triple Elimination program has been going well with many pregnant women who have high perceptions of the vulnerability of Triple Elimination, but what needs to be improved is counseling and information about HIV and HIV testing from health workers and support from related agencies so that this program runs optimally. and pregnant women are willing to carry out the Triple Elimination test.Conclusion: This study suggests the need for counseling and education on HIV testing from health workers and support from relevant agencies. Future research can look at the factors that affect the performance of health workers in providing education